Spirituality and Transformational Learning: How Urban Residents Abandoned a Life of Violence - (:unkn) unknown (My University, 2011)
Community violence has been a perpetual issue among disenfranchised, African American, urban youth around the world. Many authors argue that high rates of violence among these youth are due to macro-structural characteristics such as inequality, segregation, racial discrimination, and poverty. These macro-structural issues place stressors (social disorganization, joblessness, alienation, mistrust of police, etc.) upon inner-city neighborhoods. Previous research also infers that African American men lack the ability to non-violently cope with these stressors and strains. Thus, this qualitative narrative study investigated the role of spirituality in the transformational process of nine urban, African American men, who had abandoned a life of violence. The purpose of the study was to find out “how” spirituality aided these men in transforming from a lifestyle of violence. The study found that early childhood trauma, along with resentments and feelings of lack, and silenced emotions eventually, caused the participants acceptance, love and protection from the streets. However, living a violent street life often led to internal conflicts and the development of addictions. When the participants found themselves facing significant jail/prison time, it facilitated a process of reflection and an openness to spirituality. The spiritual quest of these individuals then led to feelings of acceptance, a renewed a sense of individual identity, provided vital networks of social support, facilitated a trusting relationship between the participants and the Creator, and provided a sense of connection with the community.
Keywords: Spirituality; Community Violence; African American Men; Transformational Process; Transformational Learning